Analisa Perbandingan Sistem Pendukung Keputusan Seleksi Penerima Beasiswa Menggunakan Metode SAW, WP, dan TOPSIS - Adinda Dwi Lestari; Aga Satria Agusta; Gustin Triani; Indira Putri Shahne; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
One of the government's concerns is to provide scholarships to students in several types of scholarships. Scholarship software is held to ease the burden on students in pursuing better education. Scholarship recipients are determined mainly based on positive standards, every possibility that is open for scholarships attracts a large number of scholarship recipients' capacity to register, but not all students who take part in scholarships have the same opportunity due to limited quotas. In this review, a case can be raised, specifically finding the best alternative based on a predetermined standard using the Simple Additive Weighting (SAW) technique, which is looking for a weighted sum of performance scores for each alternative on all criteria. The Weighted Product (WP) approach is a technique for solving various attributes, where each attribute must be sorted first with a predetermined attribute weight. technique for Desire Sequence through Similarity to an ideal answer (TOPSIS) is a scholarship choice gadget using TOPSIS with the aim to be mechanically ranked in ascending layout based on the highest vector value. The end result is that there are variations in the calculation of each saw, WP and TOPSIS method. the highest score for the saw method is Fitri, for the WP approach the highest score is Lastri and for the TOPSIS method the highest score is Sasmito.